Advances in high‐throughput experiments of polymer crystallization for developing polymer processing - Bao Deng; Jinyong Wu; Hao Lin; Ling Xu; Ganji Zhong; Jun Lei; Ludwig Cardon; Jiazhuang Xu; Zhongming Li (Materials Genome Engineering Advances)
Abstract Polymer crystallization, an everlasting subject in polymeric materials, holds great significance not only as a fundamental theoretical issue but also as a pivotal basis for directing polymer processing. Given its multistep, rapid, and thermodynamic nature, tracing and comprehending polymer crystallization pose a formidable challenge, particularly when it encounters practical processing scenarios that involve complex coupled fields (such as temperature, flow, and pressure). The advent of high‐time and spatially resolved experiments paves the way for in situ investigations of polymer crystallization. In this review, we delve into the strides in studying polymer crystallization under the effects of coupled external fields via state‐of‐the‐art high‐throughput experiments. We highlight the intricate setup of these high‐throughput experimental devices, spanning from the laboratory and pilot levels to the industrial level. The individual and combined effects of external fields on polymer crystallization are discussed. By breaking away from the conventional “black box” research approach, special interest is paid to the in situ crystalline behavior of polymers during realistic processing. Finally, we underscore the advancements in polymer crystallization via high‐throughput experiments and outline its promising development.